Timescapes in Childhood Memories of Everyday Life During the Cold War - ZIN, Mnemo; da Rosa Ribeiro, Camila (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
During the Cold War, linear and future-oriented temporalities were enforced to accelerate social transformation on both sides of the Iron Curtain. Despite efforts to control time by bracketing complex human conditions, children were routinely engaged in everyday activities that followed different rhythms. Building on Barbara Adam’s notion of timescapes and drawing on collective biography research, this article examines different temporal experiences through childhood memories of harvesting in a forest, a family garden, and a collective farm. These memories reveal emotionally intense—embodied and embedded—temporal experiences of children entangled within timescapes of multiple and sometimes contradictory dimensions of human and more-than-human times.